Spectroscopic Properties of Pr3+ Doped in Zinc Lithium Calcium Potassiumniobate Phosphate Glasses - Pankaj Deedwaniya; Meena, S.L. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Glass of the system: (45-x) P2O5:10ZnO:10Li2O:10CaO:10K2O:15Nb2O5:xPr6O11. (Where x=1, 1.5,2 mol %) have been prepared by melt-quenching method. The amorphous nature of the prepared glass samples was confirmed by X-ray diffraction. Optical absorption, Excitation and fluorescence spectra were recorded at room temperature for all glass samples. Judd-Ofelt intensity parameters Ωλ (λ=2, 4 and 6) are evaluated from the intensities of various absorption bands of optical absorption spectra. Using these intensity parameters various radiative properties like spontaneous emission probability (A), branching ratio (β), radiative life time (τR) and stimulated emission cross–section (σp) of various emission lines have been evaluated.